2023
DOI: 10.1038/s41477-022-01336-2
|View full text |Cite
|
Sign up to set email alerts
|

The F-box protein UFO controls flower development by redirecting the master transcription factor LEAFY to new cis-elements

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 87 publications
(109 reference statements)
1
34
0
Order By: Relevance
“…Even the most severe mutant phenotype of Gmufo did not show complete replacement of the second whorl organ with sepals, and sepal-like petals mostly appeared on the ventral part. Previous studies have documented that by controlling the interaction between UFO and LFY, the UFO gene can regulate the downstream targets of AP3 and PI, thereby affecting the flower phenotype [8]. In this context, the interaction among the UFO, ABC, LFY, WUS, and CAL genes has been explored previously in different studies at the petal formation stage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Even the most severe mutant phenotype of Gmufo did not show complete replacement of the second whorl organ with sepals, and sepal-like petals mostly appeared on the ventral part. Previous studies have documented that by controlling the interaction between UFO and LFY, the UFO gene can regulate the downstream targets of AP3 and PI, thereby affecting the flower phenotype [8]. In this context, the interaction among the UFO, ABC, LFY, WUS, and CAL genes has been explored previously in different studies at the petal formation stage.…”
Section: Discussionmentioning
confidence: 98%
“…LFY controls the temporal specificity of AP3 expression, while UFO and AP1 control the spatial pattern [5,6]. UFO has been reported to interact with the SCF E3 ubiquitin ligase subunits, ASK1 and CUL1, as well as subunits of the COP9 signalosome, which suggest the possible role of UFO in the ubiquitination of proteins that are involved in flower development [7,8]. The interaction of the UFO and ASK1 proteins may enhance the degradation of the downstream B functional gene AP3 and the PI inhibitor by the UFO gene, resulting in the activation and production of the B functional gene [5,9,10].…”
Section: Of 16mentioning
confidence: 99%
See 1 more Smart Citation
“…Revisiting UFO-LFY targets regulating floral organ development The role of UFO-LFY on floral organ development is established in most angiosperm species, and several target genes have been identified (see above). In Arabidopsis, such targets include the B genes AP3 for which functional LUBS were identified in their promoter sequence, explaining their regulation by the UFO-LFY complex (Rieu et al, 2023). Functional LUBS sites are expected to be found in the regulatory sequences of genes under the control of the UFO-LFY complex in many other plants, in particular B, C or E homeotic genes.…”
Section: Revisiting Ufo and Lfy Targets In Light Of The Ufo-lfy Trans...mentioning
confidence: 99%
“…In contrast to a previous study (Risseeuw et al ., 2013), it was recently found that overexpression of a truncated UFO version lacking the F‐box domain (i.e. unable to participate in a SCF complex) largely complemented a strong Arabidopsis ufo allele, restoring petal and stamen development (Rieu et al ., 2023). Hence, the connection of UFO to an E3 ligase complex appears partially dispensable, at least in Arabidopsis.…”
Section: Ufo Is An F‐box Proteinmentioning
confidence: 99%